A Novel Innate Immune-Enhancement Strategy Combined with IVIG Rescues Mice from Fatal Staphylococcus aureus Septicemia. (16th November 2011) - Rajam, Gowrisankar; Hammons, Gabrielle M.; Carlone, George M.; Sampson, Jacquelyn S.; Ades, Edwin W.
Abstract : Staphylococcus aureus (SA) is a major community-acquired pathogen. The emergence of drug-resistant strains like, methicillin-resistant SA (MRSA), poses stiff challenges to therapeutic intervention. Passive immune-therapy with specific antibodies is being actively examined to treat fulminant infections with limited success. In this study, we demonstrate that P4, a 28-amino acid peptide, derived from pneumococcal surface adhesin A along with pathogen-specific antibody (IVIG; P4 therapy) is successful in enhancing the opsonophagocytic killing (OPK) of S. aureus in vitro . We questioned if it is possible to expand P4 therapy to treat staphylococcal infections in vivo . P4 therapy in combination with IVIG rescued 7/10 morbidly ill S. aureus -infected mice while only 2/10 survived in the control group.